The Value Of Pancasila As A Moral And Ethical Foundation In The Politics Of The Nation And State - Amelia Puspita Sari; Dhea Ajeng Saputri; Dian Ayu Septiandi; Gilang Septiyawan (Citakonsultindo, 2024)
Pancasila is the basis of the state and also the view of life of the Indonesian nation which contains noble values that reflect the life of Indonesian society, because basically these values are extracted from the soul and personality of the Indonesian people since ancient times. The purpose of the research is to understand the concept of political ethics in Indonesia, as well as to understand the values of Pancasila which is used as a moral and ethical foundation in the politics of nation and state. In this study, the subject of research is literature related to Pancasila, political ethics, and what aspects are used as Pancasila values as a moral and ethical foundation in the politics of the nation and state. This research is a library research, namely library materials as the main source by collecting data and reviewing works from books, encyclopedias, dictionaries, journals, and papers. The result of this research is that Pancasila is not only a moral foundation and political ethics, but also a solid foundation in building a democratic, just and civilised nation and state politics. By internalising and applying the values of Pancasila in daily political practice, it is hoped that Indonesia can continue to develop towards a better direction, in accordance with the ideals of the nation as expressed in Pancasila